Makroekonomiczne problemy sterowania optymalnego w matematycznej teorii wzrostu - Panek, Emil (Wydział Prawa i Administracji UAM, 1984)
The work presents three tasks of optimum control of growth in a one-sector economy with a two-factor function of production of Cobb and Douglas, differing in assumptions on national income growth and consumption. Maximalization of consumption in a fixed period of time serves as a growth criterion in the first two tasks. In the third one the growth criterion being time necessary for the economy to reach a target level of consumption goods production. A certain group of conditions eliminating discontinuities („leaps") in the national income distribution revealed in the solutions of the preceding tasks was introduced here. On the marigin of the reached solutions, the author touches on certain general, as it seems, regularities, which are ruling optimum processes of growth in the long run.
Macroeconomic problems of optimum control in the mathematical theory of growth